The impact of the 2016 flood event in Anhui Province, China on infectious diarrhea disease: An interrupted time-series study. (June 2019) - Zhang, Na; Song, Dandan; Zhang, Jin; Liao, Wenmin; Miao, Kaichao; Zhong, Shuang; Lin, Shao; Hajat, Shakoor; Yang, Lianping; Huang, Cunrui
Abstract: Climate change may bring more frequent and severe floods which will heighten public health problems, including an increased risk of infectious diarrhea in susceptible populations. Affected by heavy rainfall and an El Niño event, a destructive flood occurred in Anhui province, China on 18th June 2016. This study investigates the impact of this severe flood on infectious diarrhea at both city-level and provincial level, and further to identify modifying factor. We obtained information on infectious diarrheal cases during 2013–2017 from the National Disease Surveillance System. An interrupted time-series design was used to estimate effects of the flood event on diarrhea in 16 cities. Then we applied a meta-analysis to estimate the area-level pooled effects of the flood in both flooded areas and non-flooded areas. Finally, a meta-regression was applied to determine whether proximity to flood was a predictor of city-level risks. Stratified analyses by gender and age group were also conducted for flooded areas. A significant increase in infectious diarrhea risk (RR = 1.11, 95% CI: 1.01, 1.23) after the flood event was found in flooded area with variation in risks across cities, while there was no increase in non-flooded areas. Diarrheal risks post-flood was progressively higher in cities with greater proximity to the Yangtze River. Children aged 5–14 were at highest risk of diarrhea post-flood in the flooded areas. Our study provides strong evidence that the 2016 severe flood significantly increased infectious diarrheal risk in exposed populations. Local public health agencies are advised to develop intervention programs to prevent and control infectious diarrhea risk when a major flood occurs, especially in areas close to water bodies and among vulnerable populations. Highlights: The 2016 flood event increases the risk of infectious diarrhea in Anhui Province. Diarrhea risk became progressively higher with closer proximity to the Yangtze River. Children aged 5–14 were at the highest risk of diarrhea post-flood.